Efektivitas Metode RICE dalam Penanganan Awal Cedera Sprain dan Strain pada Atlet Karate Tingkat Pemula dan Lanjutan - Herlina, Herlina; Ashari, L. Hasan (Primary Journal of Multidisciplinary Research, 2025)
This study aims to evaluate the effectiveness of the RICE (Rest, Ice, Compression, Elevation) method as an initial treatment for sprain and strain injuries among beginner and advanced karate athletes. The research background stems from the high incidence of ankle, knee, and arm injuries in karate, as well as ongoing debates regarding the relevance of the RICE method compared to newer protocols such as PRICE and POLICE. A comparative quantitative design was employed, measuring four key parameters pain intensity, edema circumference, joint range of motion (ROM), and joint stability on days 1, 3, and 5 following injury. The findings indicate that the RICE method is effective in significantly reducing pain and swelling within the first 48–72 hours after injury in both athlete groups. ROM improvements also occurred progressively, with advanced athletes demonstrating faster recovery than beginners, particularly in joint stability and functional performance. These results align with contemporary literature that highlights the benefits of ice application, compression, elevation, and controlled rest during the acute inflammatory phase. Overall, this study concludes that the RICE method remains relevant as a basic first-aid protocol for sprain and strain injuries in karate, although subsequent interventions should follow updated evidence-based practice guidelines. The results are expected to strengthen first-aid education for coaches, athletes, and sports support personnel.